1997
DOI: 10.1038/bjc.1997.196
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin B fraction active at physiological pH of 7.5 is of prognostic significance in squamous cell carcinoma of human lung

Abstract: Summary In this study we examined both the pH dependence of cathepsin B (cath B) activity and its stability at physiological pH of 7.5 in lung tumours and normal lung tissue by means of fluorogenic assays with Z-Arg-Arg-AMC as specific substrate. Specificity was verified with the cath B blocking inhibitors E-64 and CA-074. With respect to pH dependence of activity, we found a deviation from a normal-shaped pHactivity curve. Besides the typical activity peak at pH 6.0, there were shoulders at pH 4.5-5.5 and at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
30
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 27 publications
2
30
0
Order By: Relevance
“…In contrast, cath B activities (cath B AT , cath B A7.5 ) and concentration (cath B C ), measured in tumour homogenates, had no prognostic relevance in the total population of NSCLC patients in a 5-year observation period. This is in contrast to the study by Ebert et al (1994) and Knoch et al (1994), but similar to the recent study (Werle et al, 1997a). The discrepancy with earlier studies is most likely due to longer observation period of 5 years in the present study.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…In contrast, cath B activities (cath B AT , cath B A7.5 ) and concentration (cath B C ), measured in tumour homogenates, had no prognostic relevance in the total population of NSCLC patients in a 5-year observation period. This is in contrast to the study by Ebert et al (1994) and Knoch et al (1994), but similar to the recent study (Werle et al, 1997a). The discrepancy with earlier studies is most likely due to longer observation period of 5 years in the present study.…”
Section: Discussionsupporting
confidence: 82%
“…Previous studies on cath B in lung tumours, using either homogenates (Krepela et al, 1990;Sedo et al, 1991;Ebert et al, 1994;Ledakis et al, 1996;Werle et al, 1997aWerle et al, , 1997b or IHC analysis of cath B (Higashiyama et al, 1991(Higashiyama et al, , 1993Ozeki et al, 1993;Inoue et al, 1994;Sukoh et al, 1994aSukoh et al, , 1994b, showed significantly enhanced expression of the enzyme at activity and protein levels in patients suffering from NSCLC. In this study, we clearly confirmed our earlier results as we found 9.1-fold increased cath B protein concentration as well as 5.6-fold increased total cath B activity and 3.2-fold increase in the fraction of cath B activity, stable at pH 7.5 (Werle et al, 1997b) in tumour compared with normal lung tissue homogenates.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The homogenization was performed according to our published protocol. 15 Aliquots of the tissue homogenates were made and kept frozen at Ϫ80°C.…”
Section: Patients and Tumorsmentioning
confidence: 99%